Schaftoside improves HFpEF through regulation the autophagy-lysosome pathway by allosterically targeting CaMKII-δ - Haiying Zhang; Yanan Gao; Min Zhang; Zhexin Yuan; Yu Chen; Aiping Wang; Xinxing Liu; Shunchang Ji; Jianfeng Jin; Jingwei Liang; Yan Liu (Redox Biology)
Heart failure with preserved ejection fraction (HFpEF) presents a significant challenge to global healthcare systems due to its complex presentation. HFpEF presents with a normal or near-normal left ventricular ejection fraction, cardiac diastolic dysfunction, and a metabolic profile characterized by impaired inflammation and oxidative stress. There have been few valuable drug targets reported for HFpEF to date. Here, we discovered that schaftoside, an active component from licorice, has a significant protective effect on the cardiac remodeling induced by continuous infusion of angiotensin II (AngII), which leads to the HFpEF phenotype. Mechanistically, schaftoside has demonstrated the ability to ameliorate lysosomal dysfunction in both in vitro and in vivo models, thereby activating autophagy. Bioinformatic analyses based on proteome and phosphoproteome suggested that Ca2+/calmodulin-dependent protein kinase II (CaMKII) was a potential target for schaftoside. It was confirmed that schaftoside allosterically mediated CaMKII-δ conformation via targeting a unique active pocket near the ATP-binding site to inhibit protein phosphorylation and regulate the lysosomal autophagy pathway. Therefore, schaftoside represents the first small molecule identified to inhibit CaMKII-δ activity through allosteric inhibition, providing a novel candidate for alleviating cardiac metabolic imbalance in HFpEF.